Ghosts of girlfriends past [videorecording (DVD)] - Waters, Mark S., 1964-; McConaughey, Matthew, 1969-; Garner, Jennifer, 1972-; Meyer, Breckin, 1974-; Chabert, Lacey, 1982-; Forster, Robert, 1942-2019-; Douglas, Michael, 1944- (New Line Home Entertainment : Warner Home Video [distributor], 2009)
Connor Mead is the kind of guy who dumps three girlfriends - at one time and by teleconference. So when he goes home to attend his brother's wedding, he has a singular goal in mind: score with the only bridesmaid he has somehow managed to miss. But the ghost of his departed Uncle Wayne - who taught him to love 'em and then leave 'em - has another goal in mind: restore Connor's lost faith in true love. This will be a tough assignment, one that will require many past girlfriends and the ghosts of his past, present and future.